A study on the relation between film quality and deposition rate for amorphous silicon films grown by electron cyclotron resonance plasma chemical vapor deposition using H2/SiH4 - Kang, M.; Kim, J.; Lim, T.; Oh, I.; Jeon, B.; Jung, I.; An, C. (Japan Society of Applied Physics, 1997)
The relation between film quality and deposition rate of hydrogenated amorphous silicon films deposited by electron cyclotron resonance plasma chemical vapor deposition using H2/SiH4 has been investigated. The properties of amorphous silicon films were improved with increasing deposition rate; photoconductivity increased and optical band gap, full width at half maximum and the ratio of the concentration of dihydride to that of monohydride decreased. The high deposition rate was a very important factor to obtain high quality amorphous silicon films grown by electron cyclotron resonance plasma chemical vapor deposition using H2/SiH4.
Keywords: Amorphous films; Amorphous silicon; Chemical vapor deposition; Electron cyclotron resonance; Energy gap; Film growth; Hydrogenation; Photoconductivity; Plasma applications; Semiconducting silicon; Semiconductor growth; Silanes; Full width at half maximum (FWHM); Semiconducting films